2006
DOI: 10.1176/ajp.2006.163.5.885
|View full text |Cite
|
Sign up to set email alerts
|

Is Domestic Violence Followed by an Increased Risk of Psychiatric Disorders Among Women But Not Among Men? A Longitudinal Cohort Study

Abstract: 1) Psychiatric disorders pose risk for involvement in abusive relationships for both sexes; 2) partner abuse is a contributing source of psychiatric disorders among women but not among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 44 publications
5
71
2
2
Order By: Relevance
“…Both depression and PTSD are consequences of IPV, but there is also some evidence from longitudinal research (Ehrensaft, Moffitt, & Caspi, 2006) that mental health problems, such as depression and PTSD, also increase women's risk of engaging in abusive relationships. For example, in a sample of adolescent girls, depression significantly predicted dating an abusive partner (Cleveland, Herrera, & Stuewig, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Both depression and PTSD are consequences of IPV, but there is also some evidence from longitudinal research (Ehrensaft, Moffitt, & Caspi, 2006) that mental health problems, such as depression and PTSD, also increase women's risk of engaging in abusive relationships. For example, in a sample of adolescent girls, depression significantly predicted dating an abusive partner (Cleveland, Herrera, & Stuewig, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Serious mental illness influences the likelihood of being in unsafe environments and relationships (McHugo et al, 2005) and increases vulnerability to violent victimization (Briere & Jordan, 2004;Khalifeh & Dean, 2010). Analysis of prospective data has found that, in addition to the association between earlier histories of mental health disorders and subsequent entrapment in abusive relationships, women who are subjected to abusive relationships also have an increased risk of subsequent psychiatric morbidity (Ehrensaft, Moffitt, & Caspi, 2006;Zlotnick, Johnson, & Kohn, 2006). In addition, data from a systematic review (Golding, 1999) found that rates of depression declined over time once the abuse had ceased, and the severity or duration of violence was associated with the prevalence or severity of depression.…”
Section: What Are the Impacts On Physical And Mental Health?mentioning
confidence: 99%
“…Male-to-female IPV results in more negative health consequences than female-to-male IPV (Archer, 2000; Holtzworth-Munroe, Smutzler, & Sandin, 1997) and female survivors of IPV report more physical and mental health problems than women who do not report partner abuse, including increased use of general health services (Miller, Cohen, & Rossman, 1993) and greater likelihood for chronic pain, diabetes, depression, substance use, and suicide (Black et al, 2011; Campbell, Sullivan, & Davidson, 1995; Golding, 1996; Kessler et al 1994). The effect of IPV victimization on mental health consequences in women has been documented in numerous longitudinal studies (Lawrence, Orengo-Aguayo, & Brock, 2012), suggesting that IPV experiences may be important antecedents (rather than consequences) of adverse health outcomes (Ehrensaft, Moffitt, & Caspi, 2006). Male victims of IPV are also at increased risk for mental health symptoms (Hines & Malley-Morrison, 2001) and a subset are victims of severe IPV (Hines & Douglas, 2010).…”
mentioning
confidence: 99%